Effects of Self-Control Ability in Pressing Aggressive Behavior: Efek Kemampuan Kontrol Diri dalam Menekan Perilaku - Madjid, Andi Nurul Fatimah; Aswar; Tajuddin, Andi (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this research is to know the effect of self-control on student aggression behavior at Makassar National Vocational School. The population used in this study were students of Makassar National Vocational School. The sample of this research was 89 people using random sampling. The data analysis technique in this research is Simple Regression Analysis with the help of the SPSS 22 for Windows program. The results of the data hypothesis analysis show that Ha is accepted with a significant value of 0.000 <0.05. The magnitude of the influence of self-control on aggression behavior was 61.7%. This means that there is a negative effect of self-control on aggression with the correlation coefficient with simple regression analysis Y = 89.816-0.837. If the self-control variable does not exist, the value of aggression behavior is 89.816. If the value of self-control is increased by 1%, the aggressive behavior will decrease by 0.837% and vice versa